Study on the immunophenotyping of acute leukemia in chidren treated at Hue central Hospital - Tuy, Tran Thi Phuong; Thang, Nguyen Duy; Hanh, Nguyen Thi Hong; Sang, Dong Si; Hoa, Phan Thi Thuy; Cuong, Ngo Tu; Duy, Phan Hoang; Lan, Le Thi Phuong; Hien, Nguyen Thi Thu; Ha, Chau Van; Mai, Ton Nu Tra; Tuyet, Nguyen Thi Bich (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.